2020
DOI: 10.31222/osf.io/9tmua
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analyzing data of a multilab replication project with individual participant data meta-analysis: A tutorial

Abstract: Multi-lab replication projects such as Registered Replication Reports and Many Labs projects are used to replicate an effect in different labs. Data of these projects are usually analyzed using conventional meta-analysis methods. This is a valid approach, but it does not make optimal use of the available data as summary data are analyzed rather than the participant data. I propose to analyze data of multi-lab replication projects by using individual participant data (IPD) meta-analysis where the participant da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…This is a point that has been extensively documented in previous methodological literature (e.g., Burke et al, 2017 ; Legha et al, 2018 ; Riley et al, 2020 ), which contrasts typical meta-analyses, which involve two stages (first estimation of effects within studies, then across studies), against IPD meta-analyses, called in this context one-stage models (direct integration of data from several studies in a single model). This point has also been highlighted in the psychological literature, in the context of multi-lab large-scale replications (van Aert, 2020 —who also provides a tutorial for conducting IPD meta-analyses). Previous methodological and simulation work has demonstrated that meta-analyses and IPD meta-analyses converge when shared assumptions are met (Burke et al, 2017 ; Papadimitropoulou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 79%
“…This is a point that has been extensively documented in previous methodological literature (e.g., Burke et al, 2017 ; Legha et al, 2018 ; Riley et al, 2020 ), which contrasts typical meta-analyses, which involve two stages (first estimation of effects within studies, then across studies), against IPD meta-analyses, called in this context one-stage models (direct integration of data from several studies in a single model). This point has also been highlighted in the psychological literature, in the context of multi-lab large-scale replications (van Aert, 2020 —who also provides a tutorial for conducting IPD meta-analyses). Previous methodological and simulation work has demonstrated that meta-analyses and IPD meta-analyses converge when shared assumptions are met (Burke et al, 2017 ; Papadimitropoulou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 79%
“…The parameter τ 2 reflects the between-study variance in true effect size and indicates whether the lab's true effect sizes θ i are all the same (homogeneous) or different from each other (heterogeneous). Heterogeneity in true effect size can be explained by extending the statistical model in (1) to a random-effects meta-regression model where study characteristics are included as moderators (e.g., Thompson & Sharp, 1999;Van Houwelingen et al, 2002). That is, a lab's true effect size becomes a regression equation in a random-effects meta-regression model (e.g., β 0 + β 1 x where x is a moderator variable).…”
Section: Statistical Modelmentioning
confidence: 99%
“…The study was replicated in 22 labs and the total sample size was 7,373 (see McCarthy et al, 2018 for more details). All analyses were conducted in the statistical software R (Version 4.1.0, R Core Team, 2021), the R package papaja (Aust & Barth, 2020) was used for writing the article, and annotated R code to analyze the RRR is available in the supplemental materials at the Open Science Framework (OSF; Van Aert, 2019a: https://osf.io/c9zep/).…”
Section: Example Of a Registered Replication Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, accessing raw participant data rather than summary data allows for testing relevant research questions while increasing statistical power to detect individual-level interactions and modeling the sources of within-and between-study variance. Furthermore, IPD meta-analysis represents a tool for evaluating replication in multi-lab studies (van Aert, 2020).…”
Section: Complex Sampling Surveysmentioning
confidence: 99%